2022
DOI: 10.3390/insects14010033
|View full text |Cite
|
Sign up to set email alerts
|

Warming in Cold Seasons Increases the Abundance of Ground-Dwelling Collembola in Permafrost Wetlands

Abstract: The consideration of environmental factors has long been crucial to developing theories about the spatial variability of species diversity. However, the effects of global warming on Collembola, in permafrost wetlands, are largely unknown. Understanding how Collembola are affected by climate warming is important as they directly affect the community assembly and decomposition processes of plant litter within soil ecosystems. A peatland area in a cold temperate monsoon climate zone in the Great Hing’an Mountains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
0
1
Order By: Relevance
“…As Sphagnum mosses provide habitat, and buffer changes in soil moisture due to their high water holding capacity (Bengtsson et al, 2020), reductions in Sphagnum cover could mechanistically explain the reductions in microarthropod richness that would potentially face unfavourable drier conditions. Contrary to what we found, Zhang et al (2023) using open-top chambers (OTCs) in a wetland in China showed that warming did not influence the richness of Collembola under warming-induced drier conditions. We posit that our lower collembolan richness under drier conditions might be explained by migration of species downward, as seen for a blanket bog in Sweden in Krab et al (2010), who also suggested that the combined Frontiers in Environmental Science frontiersin.org effects of higher temperatures and lower moisture levels may cause desiccation stress and strongly influence the vertical stratification of collembolans.…”
Section: Discussioncontrasting
confidence: 99%
“…As Sphagnum mosses provide habitat, and buffer changes in soil moisture due to their high water holding capacity (Bengtsson et al, 2020), reductions in Sphagnum cover could mechanistically explain the reductions in microarthropod richness that would potentially face unfavourable drier conditions. Contrary to what we found, Zhang et al (2023) using open-top chambers (OTCs) in a wetland in China showed that warming did not influence the richness of Collembola under warming-induced drier conditions. We posit that our lower collembolan richness under drier conditions might be explained by migration of species downward, as seen for a blanket bog in Sweden in Krab et al (2010), who also suggested that the combined Frontiers in Environmental Science frontiersin.org effects of higher temperatures and lower moisture levels may cause desiccation stress and strongly influence the vertical stratification of collembolans.…”
Section: Discussioncontrasting
confidence: 99%